ANALISIS PERENCANAAN KEUANGAN SYARIAH DALAM MENINGKATKAN KESADARAN PETANI JAGUNG TERHADAP ZAKAT DI NAGARI KOTO RAJO KABUPATEN PASAMAN (Studi Kasus: Petani Jagung Di Nagari Koto Rajo Kabupaten Pasaman) - Junianti Junianti; Rahmikhatib Rahmikhatib (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
Thesis with the title "Analysis of Sharia Financial Planning in Increasing Corn Farmers' Awareness of Zakat in Nagari Koto Rajo, Pasaman Regency". Compiled by Junianti Nim 3321328 Sharia Banking Study Program, Faculty of Islamic Economics and Business, State Islamic University (UIN) Sjech M.Djamil Djambek Bukittinggi. The problem is that there has been a mismatch between theory and practice, which is due to the fact that there are still many people who do not understand how to manage finances, especially corn farmers, which can result in them often lacking business capital to replant, as well as decreasing contributions to zakat, even though on the other hand, sometimes the income from corn farming has reached the nisab for paying zakat. The aim of this research is to find out how Sharia Financial Planning Analysis Increases Corn Farmers' Awareness of Zakat in Nagari Koto Rajo, Pasaman Regency. This research is a type of qualitative research using data collection techniques. The data used are primary and secondary data obtained from respondents through observation, interviews and documentation. The results of this research show that of the 20 corn farmers the author interviewed, the income obtained from corn farming has all reached the nisab for zakat. However, of these 20 people, only 10 farmers understand about paying zakat and have paid zakat from their agricultural products, 10 more farmers do not understand about zakat from agricultural products and have not paid zakat.